ANALSIS PERHITUNGAN HARGA POKOK PROYEK PERBAIKAN JALAN PADA PT HARLIS TATA TAHTA - MUHAMMAD ADHITYA FARYANSA; SITI MASYITHOH; DHINA MUSTIKA (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
The purposes of this reseach is to know th basic cost of according to company and for to compare basic cost of project from accounting theory with company.     The basic theory that used by cost accounting and project management is using the tool of basic cost of project analysis. Based on result of analysis and discussion, therefore the conculsions from the research is The basic cost of project according to accounting theory is Rp.12.807.087.136 that consist Rp.11.900.790.594 for raw material cost, Rp. 503.578.423 for direct labor cost, and Rp. 402.718.119 for overhead cost. The basic cost of project according to company is Rp. 12.887.496.368, that consist Rp. 11.900.790.594 for raw material cost, Rp. 666.500.447 for labor cost, and Rp. 320.205.327 cost of equipment. Based on the result of calculate above, in fact, the difference basic cost of project between company and the theory is Rp. 80.409.232. It because there are many items cost that must not included into basic cost of project but it has included by yhe company. Thus, the research that the calculate of basic cost of project from Company is greater than the theory accpeted.       Keywords: Cost accounting, Project management, The cost of the project